Let it Snow - John Green; Maureen Johnson; Lauren Myracle (USA Penguin Group, 2008)
An ill-timed storm on Christmas Eve buries the residents of Gracetown under multiple feet of snow and causes quite a bit of chaos. One brave soul ventures out into the storm from her stranded train and sets off a chain of events that will change quite a few lives. Over the next three days one girl takes a risky shortcut with an adorable stranger, three friends set out to win a race to the Waffle House (and the hash brown spoils), and the fate of a teacup pig falls into the hands of a lovesick barista. A trio of today's bestselling authors - John Green, Maureen Johnson, and Lauren Myracle- brings all the magic of the holidays to life in three hilarious and charming interconnected tales of love, romance, and kisses that will steal your breath away.
Keywords: Fiction; Young Adult; Short Stories; Holiday; Romance